Challenges of performing prayer in the research field for Muslim researchers at public universities - Mutalib, N. A.; Embong, A. H.; Ismail, I. L. M.; Mokhtar, W. K. A.W.; Agadirun, N. D.; Chua, N. A.; Halim, A. A.; Azmi, R.; Azhar, A.; Hasbullah, M. M. (Universiti Sultan Azlan Shah, 2024)
Every Muslim is required to perform the five daily prayers regardless of time and place because it is a highly demanded act of worship in Islam. At the higher education level in Malaysia, numerous Muslim researchers are engaged in various fields of study, including the sea, forests, mangroves, and similar areas. They encounter difficulties when it comes to performing their five daily prayers, particularly when it comes to the specific procedures involved in these fields. The purpose of this study is to identify the issues and challenges researchers face in praying while conducting research. This study is qualitative in nature, employing structured interview methods, and its respondents are researchers and postgraduate students from public universities, including Universiti Putra Malaysia (UPM), Universiti Sains Malaysia (USM), and Universiti Malaysia Terengganu (UMT). We used Atlas.ti to thematically analyze the data from this interview, obtaining accurate findings based on specific themes. The study findingsindicate that there are various challenges faced by researchers in performing the prayer ritual while in the field. This study recommends publishing a guideline on the procedures for conducting prayers in the field as a reference for the involved researchers.